2000
DOI: 10.1021/ma992000t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Regioregular Polymers Containing Substituted Thienylene/Bithienylene and Phenylene Repeating Units

Abstract: Regioregular polymers poly(3-alkyl-2,5-thienylene-alt-1,4-phenylene) (PBTCn, n ) 4, 8, 12) and poly [1,4-bis(3-alkyl-2-thienyl)phenylene] (PBTBCn, n ) 4, 8, 12), which contain alternating phenylene and substituted thienylene or bithienylene repeating units, have been chemically and/or electrochemically synthesized and characterized. Their structures are consistent with that expected as indicated by NMR, FTIR, and microanalysis. The change in glass transition temperature and UV-vis and fluorescence spectra with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 50 publications
4
29
0
Order By: Relevance
“…In addition, PBHThBe film presents dual-color electrochromism, which exhibits yellow (neutral state) and blue (doped state) during the redox loop. Structurally similar polymers were reported by Reynolds and co-workers [18] and Chan and co-workers [17] to show very similar phenomena. Table 1 reveals the electrochromic switching behavior of PBHThBe film monitored at 396 and 1100 nm in 0.1 M LiClO 4 / ACN solution between 0.60 V and 1.10 V with a residence time of 8 s. The optical contrast (DT%) for PBHThBe at 396 nm and 1100 nm are 24% and 30%, respectively.…”
Section: Spectroelectrochemical Property and Electrochromic Switchingsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, PBHThBe film presents dual-color electrochromism, which exhibits yellow (neutral state) and blue (doped state) during the redox loop. Structurally similar polymers were reported by Reynolds and co-workers [18] and Chan and co-workers [17] to show very similar phenomena. Table 1 reveals the electrochromic switching behavior of PBHThBe film monitored at 396 and 1100 nm in 0.1 M LiClO 4 / ACN solution between 0.60 V and 1.10 V with a residence time of 8 s. The optical contrast (DT%) for PBHThBe at 396 nm and 1100 nm are 24% and 30%, respectively.…”
Section: Spectroelectrochemical Property and Electrochromic Switchingsupporting
confidence: 86%
“…In order to overcome these drawbacks, various thiophene-based oligomers have been invented [15,16]. Recently, Chan and co-workers have reported a serial of oligomers containing alternating phenylene and alkyl-substituted thienylene units whose polymers are regioregular and soluble in organic solvents [17]. Reynolds and co-workers have designed three discrete oligomeric systems and have successfully constructed the first oligomer-based photopatterned EC device [18].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, great efforts have been made in polymer science for better elucidation and prediction of the structure and properties of synthetic polymers [10][11][12]. In this paper, the first study of the optical properties of thin films of thienylene-dialkoxyphenylene is reported.…”
Section: Introductionmentioning
confidence: 99%
“…[25,26]. For the synthesis of the tetra-fluorinated "in" alkylated compound (D), magnesium and a catalytic amount of iodine were stirred with anhydrous THF at reflux.…”
Section: Synthesismentioning
confidence: 99%